A Study of Adverse Effects Following Administration of Anti-Rabies Vaccination - A Hospital Based Study - Panda, Manasi; Kapoor, Richa (National Journal of Community Medicine, 2022)
Rabies is an acute viral zoonotic disease that affects all warm-blooded animals including mammals and occurs in more than 150 countries and territories. Although rabies is a 100% fatal disease, it can be prevented by the use of potent anti-rabies vaccines (ARV). The present study was a hospital based descriptive longitudinal study conducted during February 2019 to July 2020 amongst the animal bite patients attending the Anti -Rabies clinic (ARC) of Vardhman Mahavir Medical College and Safdarjung Hospital (VMMC & SJH), New Delhi, to study the adverse events (vaccine reactions) if any following administration of the ARV. The age of the study participants ranged from 2 to 65 years and the mean age was (29.3±15.2) years. No severe or serious adverse events were reported. Of the minor reactions, the most commonly reported symptom was pain at the injection site (34; 9.4%) followed by occurrence of tingling sensation (29; 8.1%), headache (22; 6.1%) and itching at the injection site (19; 5.3%). These findings corroborate with those found in previous studies in the literature. It was concluded that although there are possible local or mild or systemic adverse reactions to rabies vaccination, but once initiated, rabies prophylaxis should not be interrupted or discontinued.